Gender, Age, and Sexual Satisfaction - Zelenbrz, Jelena (2003)
Our presentation analyzes the structure and dynamics of sexual satisfaction in a random sample of over seven hundred metropolitan women and men aged 20-60. We test several hypotheses, informed by both evolutionary and social constructivist theory, about the influence of gender and age on sexual satisfaction. The results point out the considerable overlap between the correlates of male and female sexual satisfaction with partner's satisfaction being the strongest predictor. In spite of the predicted decline in sexual interest, sexual satisfaction does not seem to be diminishing with age. In the concluding section, the authors discuss the findings in regard to the sexual dynamics within long-term intimate relationships.